Do Consumers Acculturated to Global Consumer Culture Buy More Impulsively? The Moderating Role of Attitudes towards and Beliefs about Advertising. Issue 4 (8th August 2019) - Czarnecka, Barbara; Schivinski, Bruno
Abstract: This research advances knowledge that can foster understanding of how global consumer culture (GCC) and its elements relate to impulsive buying and sheds light on how advertising attitudes and beliefs interact with this main relationship. Specifically, this study examines the moderating effects of attitudes towards and beliefs about advertising on the relations between consumers' level of acculturation to global consumer culture (AGCC) and impulsive buying. Consumers who are the most acculturated to GCC, and who have positive attitudes towards and beliefs about advertising, buy the most impulsively. AGCC is related to increased impulsive buying, even when attitudes towards and beliefs about advertising are negative. The article contributes to the development of a theoretical explanation of these understudied relations by employing acculturation theory and congruity theory. Social and practical implications are discussed.